The Influence of Kopiko Product Advertisement on the Enhancement of Brand Awareness - Maya Desvita Sari (International Journal Administration, Business & Organization, 2022)
This research aims to investigate The Influence of Kopiko Product Advertisement on the Enhancement of Brand Awareness in the Korean Drama "Vincenzo". The study utilizes a quantitative descriptive analysis method with data analysis methods including descriptive tests, correlation, and regression. Exploring the extent to which the portrayal of Kopiko products in the context of South Korean television drama can affect brand awareness among viewers. Data collection for this research employs a questionnaire distributed through social media to students at the Bandung State Polytechnic, Indonesia with 111 respondents obtained. The outcomes of this research are expected to provide insights into the effectiveness of marketing strategies through product placement in global entertainment productions such as Korean dramas, particularly in enhancing brand awareness for specific products.